(untitled) (Raparin Journal of Humanities (RJH), 2026)
This research tries to examine and analysis the changes that occurred in Turkey’s strategy towards the European Union from 2002 to 2024. The Turkish strategy towards the European Union underwent several stages. During the Justice and Development Party’s rule, this strategy converged through accession negotiations with intensive diplomatic activity. Then, there was a divergence and a lukewarmness between the two sides due to various reasons. Therefore, in this study, we focused on the efforts made by Turkey to join the European Union after 2002, as this period witnessed two expansions in 2004 and 2007, an obstacle during constitutional and legal reforms to meet the Copenhagen criteria. Then we touched on the change that occurred in the Turkish strategy that made the European Union, in particular, after 2007, and the transformation of this strategy towards the Middle East and the BRICS countries, especially Russia and China. Based on these data and transformations, the study tries to answer the primary question: What explains the change in the Turkish strategy towards the European Union? . It can be concluded that the change in the Turkish strategy towards the European Union occurred as a result of multiple reasons related to the European demands related to the Copenhagen criteria and the fear of some European countries of Turkey’s accession to the European Union, in addition to the changes that occurred in the regional and international environment, which prompted the ruling Justice and Development Party to diversify its strategic partners.